Effects of Classroom Practices and Funding Streams on Early Childhood Learning Outcomes. Issue 2 (17th February 2021) - Ma, Xin; Shen, Jianping; Brandi, Karen; Lu, Xuejin; Baron, Marc
ABSTRACT: Research Findings : Using a stratified random sample of 1494 preschoolers from 387 classrooms, we examined the relationship of early language and cognitive outcomes of children to classroom practices of early care and education practitioners and funding streams at various administrative levels in a survey-based pretest-posttest design. Results of hierarchical linear modeling (HLM) identified the robust effects of classroom organization on emergent literacy even after control over funding streams. After controlling for classroom practices, we identified the effects of three funding patterns. In a stimulating pattern, a combination of certain funding streams was effective in promoting emergent literacy. In an interfering pattern, a combination of certain funding streams undermined both mathematics skills and emergent literacy. In a replacing pattern, individual funding streams operating alone were not adequate to help falling-behind children. Policy or Practice : Professional development designed for preschool practitioners may want to include practical strategies to improve classroom organization. In seeking cooperation among funding streams to overcome the inadequacy of individual funding streams working alone, policymakers and educators should become aware of both the stimulating pattern and the interfering pattern.